Penggunaan Framework Laravel Pelayanan Reservasi Kamar Berbasis Web di Renz Hotel Pangkalpinang - Lili Indah Sari; Wishnu Aribowo Probonegoro; Parlia Romadiana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Ren'z Hotel Pangkalpinang is a hotel that is strategically located in the middle of Pangkalpinang City. The reservation service or room reservation that he does is still conventional, that is, it is recorded in a book and entered into a computer using Microsoft Excel (spreadsheet). Guests who make room reservations to stay can only be done by telephone, or come in person. The existence of a human error factor in the process of recording room reservations causes frequent errors in recording room reservations, the length of information in checking the status of the room is filled or empty or has been ordered. The existence of these problems is the background of the author to conduct research at this Ren'z Hotel. The web-based hotel system will make it very easy for prospective guests who will make reservations or room reservations without having to come to the hotel first. It is hoped that with this system ordering can be faster, more precise, accurate and improve a quality performance and also provide information services to consumers. The research method carried out by the author is the method of collecting data in the form of observations, interviews and literature studies, while the system development method uses the waterfall by using tools in the form of UML (Unified Modeling Language) and making the application using the Laravel Framework.